(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This paper deals with the project Bambino Manifesto, concerning Virgilio Sieni’s creation and exhibition of 5 manifestos based on photographs of a group of children depicting gestures from Masaccio and Masolino’s Storie di San Pietro, frescoed at the Cappella Brancacci in Florence. The pictures are explained both as deriving from a balance between form and dynamics, that is put in motion by a detailed work on the dancing body, and as events in themselves being ‘enacted’ by the spectators encountering them, whether casually or purposefully, while walking in the city streets. In fact, the process anticipating and following the elaboration of the pictures comes to affect and determine the photographs performative and aesthetic value. Movement analysis, historical contextualization, as well as the ideas of punctum (Barthes), of building duration (DidiHuberman) and of the theatricality of photographs (Maria Ines Aliverti) serve as a methodological interdisciplinary basis for this study, which shows the intertextual nature of such artistic objects and the semantic and symbolic network they activate in their observers’ eyes.